A study on intelligent building concepts in Putrajaya / Wan Rohaiza Wan Muhammad - Wan Muhammad, Wan Rohaiza (Faculty of Business and Management, Universiti Teknologi MARA, 2007)
The aim of this dissertation is to understand what intelligent building, the concept and the characteristics. It describes the basic concept of intelligent building that must apply. It also highlights the intelligent building design, construction and operation. Three Intelligent Buildings were selected as case studies, which are:1. Kompleks Perbadanan Putrajaya2. Kementerian Belia & Sukan3. Putrajaya International Convention Centre The aim of this dissertation is to understand what intelligent building, the concept and the characteristics. It describes the basic concept of intelligent building that must apply. It also highlights the intelligent building design, construction and operation. This dissertation also will highlight the effectiveness of management system and operation of case studies. It is to know how far the effectiveness can be achieved through intelligent management. At the end of this dissertation, recommendations and conclusion that are developed through my observations of the professional opinions gathered throughout this study is presented.